The Effect of the Aminic Substituent on the Thermal Decomposition of Cyclic Dithiocarbamates - Cavalheiro Éder T.G.; Ionashiro Massao; Marino Glimaldo; Breviglieri Susete T.; Chierice Gilberto O. (Journal of the Brazilian Chemical Society, 1999)
Thermogravimetric and Differential Scanning Calorimetric investigation of the thermal behaviour of NH4+, Na+, Zn2+, Cd2+ e Pb2+ dithiocarbamates obtained from cyclic amines, is described under nitrogen and air atmospheres in order to investigate the effect of a cyclic ring on the mechanism of decomposition. Intermediates were identified by X-ray Diffraction analysis. Zn2+, Cd2+ e Pb2+ oxysulphates were detected under air atmosphere suggesting the thermal decomposition under these conditions as an alternating synthetic route to prepare those compounds. The final decomposition products were the metallic sulphides under N2 atmosphere while transition metal oxides and sodium sulphate were obtained under air. Melting enthalpies are also reported from DSC data.